The Effectiveness of a School-based Self-injury Prevention Program on Reducing Interpersonal Cognitive Distortion and Fear of Negative Evaluation in Adolescent Girls - Sajjad Rezaei; Kamran Sheivandi Cholicheh; Esmaeil Sadipour; Neda Nezhadhamdy; Fariborz Dortaj (Caspian Journal of Neurological Sciences, 2022)
Background: Non-Suicidal Self-Injury (NSSI) is a prevalent, harmful, and transdiagnostic behavior that can comprehensively be assessed in daily life studies. Objectives: This study aimed to determine the effectiveness of the student self-injury prevention program in mitigating the Interpersonal Cognitive Distortion (ICD) and the fear of Negative Evaluation (FNE). Materials & Methods: This research is a quasi-experimental study with a pre-test-post-test design, a one-month follow-up, and a control group. The statistical population consisted of all female adolescents studying at the middle schools of Rasht City, Iran, in the 2019–2020 academic years. They must have experienced self-injury at least once. The purposive non-random sampling technique was employed to select 34 self-injuring adolescents, who were then randomly assigned to case and control groups. The interpersonal cognitive distortion scale and the brief fear of negative evaluation scale were adopted to collect data. The case group received 16 sessions of self-injury prevention training for students (twice a week), whereas the control group had no training programs. Analysis of variance and multivariate analysis of variance were then used for data analysis in SPSS v. 25. Results: The results demonstrated the significant effectiveness of the training program in mitigating the ICD (interpersonal rejection: P<0.01; F=21.780, unrealistic relationship expectations: P<0.01; F=51.096, interpersonal misperception: P<0.01; F=20.557), reducing negative meta-emotion, and increasing positive meta-emotion (P<0.05; F=43.591). Conclusion: The student self-injury prevention program effectively reduced the ICD and FNE of female adolescents. Additionally, these two variables have high levels in adolescents struggling with self-injury.